Cyclic regeneration and up-concentration for nitrate recovery from wastewater via in situ NaNO3 generation under saline, fully autotrophic nitrification conditions - Molin Lian; Zihang Ma; Guang Chen; Siqi Yu; Qing Xia; Bingjie Lin; Xiangdong Xu; Rui Tang; Zhen Zhou (Bioresource Technology, 2026)

Efficient sludge reduction and phosphorus recovery in innovative coupled sequencing batch and worm reactor Process: Performance, mass balance and metagenomic mechanisms - Jingjing Zhang; Lipin Li; Xuanhe Yang; Siqi Chen; Zhe Li; Rui Li; Chunlei Wang; Yu Tian (Bioresource Technology, 2026)

Integrative multi-omics analysis identifies FAM3D as a prognostic tumor suppressor in cervical cancer - Yanbin Chen; Yu Hong; Dongjun Wei; Lianjiao Fan; Dian Tao; Rui Zhang; Hongwei Yang (Functional & Integrative Genomics, 2026)

A reproducible endothelial-state contrast with limited bulk prognostic robustness in hepatocellular carcinoma - Si-yuan Tan; Lan-hui Qin; Wenqing Liang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Yu Zhang; Liling Long (Functional & Integrative Genomics, 2026)

State-dependent alterations of network characteristics between seizure and non-seizure onset zones in drug-resistant epilepsy - Kunlin Guo; Kunying Meng; Renping Yu; Lipeng Zhang; Yuxia Hu; Rui Zhang; Dezhong Yao; Mingming Chen (Cognitive Neurodynamics, 2026)

Safety and efficacy of recombinant botulinum toxin type A (Eveotox®) in patients with post-stroke upper limb spasticity: Results from a Phase Ib/II clinical trial - Rongrong Lu; Lingjing Jin; Jianzhong Xiong; Lixin Zhang; Yaling Liu; Leilei Xu; Rui Wu; Jianhua Tang; Liandong Zhao; Lihua Dong; Weifeng Luo; Yu Pan; et al. (Toxicon, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Generalizable structural behavior modeling with synthetic pretrained tabular transformer network for dam health monitoring - Shun Qin; Qiubing Ren; Mingchao Li; Yantao Yu; Yingbo Chen; Rui Kong (Engineering Structures, 2026)

An enhanced bounding surface model with modified plastic flow rule for cyclically loaded clay: Formulation, implementation, and dynamic finite element analysis - Kehao Chen; Rui Pang; Bin Xu; Long Yu; Yang Zhou (Computers and Geotechnics, 2026)

Constructing a dual-active-phase Li4SiO4/Li3NaSiO4 system through Na2CO3/NaCl codoping for enhanced thermochemical energy storage - Jian Chen; Rui Shen; Yan Qi; Hanlei Yu; Tao Fang; Xue Bu; Ziheng Xu; Han Ye; Youshi Li; Bocheng Yu; Hui Zhou (Chemical Engineering Journal, 2026)

Design of a biomimetic walking wheel inspired by reindeer hoof morphology and its snow-terrain locomotion performance - Kaixiang Chen; Rui Zhang; Mingxi Yu; Huailiang Wang; Hao Pang; Lige Wen (Cold Regions Science and Technology, 2026)

Nitrogen and straw optimization boosts rice growth via arbuscular mycorrhizal fungal communities and soil ecological functions - Rui Chen; Ning Wang; Pei Chen; Yu Cheng; Jian-Guang Yu; Li-Hong Xue; Lin-Zhang Yang (Applied Soil Ecology, 2026)

Microbiome dysbiosis and metabolic reprogramming in kiwifruit peel during Botrytis cinerea infection - Jingsheng Chen; Rui Ma; Yu Zhao; Yuan Sui; Zhuo Chen; Xianmei Xiao; Zhenshuo Wang; Jia Liu (Postharvest Biology and Technology, 2026)

Viscoelastic response of composite tensile armor layers in flexible risers under axial random loading - Rui Bao; Chen An; Ming Wang; Yu Zhang; Changyun Li (Ocean Engineering, 2026)

Catalytic ozonation with N, S co-doped sludge biochar for decontamination: Performance and mechanistic insights - Xinyi Tao; Weiwei Chen; Xuehong Fan; Rui Hu; Xuejian Wang; Shiquan Sun; Yu-Hong Cui; Zheng-Qian Liu (Journal of Environmental Chemical Engineering, 2026)

A multiomics perspective on ecological toxicity, environmental behavior, and synthetic microbiome restoration of RDX in soil - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Yu Zhang; Xue-gang Luo (Journal of Environmental Chemical Engineering, 2026)

Climate and soil shape Daqu wheat quality and seed microbiome via rhizosphere taxa and microbial assembly - Kangjie Yu; Shuanghui Wang; Hanrui Shi; Rui Luo; Zijian Chen; Yi Xia; Qingdong Zeng; Yi Ma; Dejun Han (Food Research International, 2026)

Synergistic effect of alkaline and heat treatment in inhibiting syneresis of CaSO₄-induced cold-set peanut protein isolate gel: Insights into structural modifications and gelation kinetics - Jing Chen; Rui Li; Zining Fan; Yu Wang; Yuntao Wang; Yanhong Bai (Food Chemistry, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Amplitude-controlled dynamic structural colors on wrinkling surfaces for facile multilevel strain-resolved optical encryption - Dengchong Feng; Shirui Wu; Yuxin Liu; Qi Guo; Rui Chen; Yu Chen; Yuzhao Yang; Haiqiang Wu; Zhiquan Zhao; Shaolin Lu; Zetong Ma; Cheng Wang; et al. (Chemical Engineering Journal, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Freeze-thaw damage evolution and crack propagation failure mechanism of red sandstone under non-uniform water distribution conditions - Li Wenbo; Sun Jielong; Chen Rui; Wang Yu; Wen Ziyi; Lou Bing (Transportation Geotechnics, 2026)

YY1/HIF-1α/NDUFA4L2 signaling axis mediates bisphenol A-induced mitochondrial dysfunction and apoptosis in human ovarian granulosa cells - Libin Xue; Cairong Chen; Yinghe Zhao; Shengtao Ma; Yingxin Yu; Song Quan; Rui Hua (Reproductive Toxicology, 2026)

Critical review on strategies for the removal of antibiotics from water and wastewater: Present situation, challenges, and perspective - Ruiwu Zhou; Wei Pan; Weichao Huang; Ping Yu; Binrui Chen; Ruizhe Zhao; Lirong Chen; Rui Tang (Process Safety and Environmental Protection, 2026)

A 4000-year record of palaeoflood activity in the lower Yellow River: identification, characteristics, and drivers from Qingqiu Mound sediments - Rui Zhang; Zhanfang Hou; Jinjia Wu; Xuexiang Chen; Shi-Yong Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Engineered probiotic carriers enregulate coordinated cuproptosis and ferroptosis with immune activation against bladder cancer - Anguo Zhao; Rongkang Li; Rui Liang; Qi Zhuang; Yang Liu; Dashi Deng; Peng Yu; Lei Peng; Hongbo Xu; Jun Zhang; Zhangxin He; Xin Chen; et al. (Chemical Engineering Journal, 2026)

Single atom anchored covalent organic framework assisted with machine learning for high-throughput pesticides discrimination - Rui Bai; Nan Chen; Chenchen Gong; Yanting Liu; Shasha Lu; Jianyu Yang; Qiulin Li; Yu Gu; Changming Li; Chunxian Guo (Chemical Engineering Journal, 2026)

A green closed-loop strategy for tin recovery and waste minimization in electroplating factories - Suiyi Zhu; Htet Oo Kaung; Minglin Zheng; Wensheng Qin; Md. Shafiqur Rahman; Yu Chen; Jiancong Liu; Zhou Rui (Clean Technologies and Environmental Policy, 2026)

Adaptability of Chaetomorpha valida (Ulvophyceae) spores to salinity, nutrients and water flow in aquaculture ponds and its invasive evaluation - Dongyue Li; Ronglian Xing; Rui Li; Xuebin Cao; Shujun Hu; Xiaojing Pan; Hongxia Zhang; Lihong Chen; Zhen Yu (Aquatic Ecology, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Calcium-mediated catalytic ozonation for water purification: Synergistic interplay among surface acid-base sites, alkaline interfacial microenvironment and dynamic oxygen supplementation - Hong-Guang Li; Cheng Chen; Zhi-Hang Wu; Ai-Yong Zhang; Rui-Gang Zhang; Shao-Wei Yuan; Ming Du; Jing-Yu Zhang (Water Research, 2026)

Effects of Alhagi sparsifolia root content and soil moisture content on soil deformation and strength under different freeze-thaw temperature conditions - Meixue Zhang; Qinglin Li; Xuanbing Luo; Wenjuan Chen; Rui Wang; Shuailong Yu; Guang Yang (Soil and Tillage Research, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Transgenic CncC overexpression confers low-level but broad-spectrum insecticide resistance in Plutella xylostella - Huichao Wang; Shiqi Chen; Rui Hu; Zhenyu Cheng; Yu Shi; Shuwen Wu; Xingliang Wang (Pesticide Biochemistry and Physiology, 2026)

Chemical constituents from Litsea pungens and their anti-inflammatory and cytotoxic activities - Kexin Chen; Fang Yang; Si-Yu Hu; Yu Zhang; Chuanrun Li; Yongxu Zhao; Chuan-Rui Zhang (Phytochemistry Letters, 2026)

Improving spatiotemporal assessment of watershed soil redistribution by integrating source-sink theory into a multi-model framework - Rui Tan; Yu Tao; Geng Guo; Kaiwen Huang; Zicheng Liu; Lin Chen; Xin Liu; Jie Lin (Journal of Hydrology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Genetic discrimination of the Dongshan Pb-Zn-Cu deposit based on sphalerite chemistry - Yi-Chen Chen; Shi-Jiong Han; Cheng-Gang Cao; Jun-Wei Bo; Yu-Rui Yuan; Ming-Yu Tang; Jin-Xin Yuan (Journal of Geochemical Exploration, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Design, preparation and performance study of DAP-1 based conductive energetic composite - Wan-Jun Wei; Rui Pu; Yu-Ruizhi Lin; Ying-Qi Mao; Qi-Long Yan; Shao-Li Chen (Chemical Engineering Journal, 2026)

Electron-networking Cu single atom-spurred Ru clusters for anion exchange membrane water electrolysis - Zihao Zhou; Rui Qin; Tingjie Mao; Pinlin Wang; Zhongliang Huang; Ting-shan Chan; Yu-cheng Huang; Zhiwei Hu; Xiaoqing Huang; Nanjun Chen; Yunhua Li (Chemical Engineering Journal, 2026)

Efficient alcoholysis of saponins to diosgenin catalyzed by sulfonated biochar from Dioscorea zingiberensis residue - Wenbing Yu; Lishan Chen; Han Yin; Rui Lu; Zhenggang Liu; Fang Lu (Bioresource Technology, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Flexotronic effect-triggered channel switching for high-sensitivity mechanical sensing - Jinwan Chen; Qing Zhao; Zhuangzhuang Zhang; Rui Ge; Hao Sun; Yongkang Zhang; Runze Yu; Longfei Wang; Shuhai Liu (Science Bulletin, 2026)

RNA warfare: Long non-coding RNAs in plant–microbe cross-kingdom regulation - Rui-Rui He; Jie Jiang; Yang Yu; Yue-Qin Chen (Molecular Plant, 2026)

How to make big data accessible to plant biologists and beyond: Ten years of lessons from TBtools - Junting Feng; Chengjie Chen; Ya Wu; Longjiang Fan; Zhang Zhang; Ming Chen; Haibao Tang; Guangchuang Yu; Jian Ren; Jingchu Luo; Yi Liao; Aiping Luan; et al. (Molecular Plant, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Heterogeneity of REE distribution revealed by rare-earth phosphate minerals in Chang’e-6 lunar soil - Zhenhao Hu; Rui Li; Jingwen Liu; Yang Li; Tao Chen; Qinglong Yu; Xi Wang; Baochen Yang; Jingyan Xu; Xiongyao Li; Jianzhong Liu; Ziyuan Ouyang (Acta Geochimica, 2026)

Glucose stabilizes the KLF5 transcription factor to promote glycolysis and malignancy of basal-like breast cancer - Rui Liu; Yu Tang; Wenjing Liu; Chunli Zhou; Zhongmei Zhou; Wen Liu; Qiang Yu; Longlong Zhang; Jian Sun; Jing Peng; Yongchun Zhou; Dewei Jiang; et al. (Science Bulletin, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Evolution of aromatic structure effect on pores and gas adsorption capacity during coalification stage - Zhen Shen; Caineng Zou; Hanlin Liu; Qun Zhao; Yanpeng Chen; Yu Song; Tengwei Gao; Rui Chen; Yu Liu (Journal of Environmental Chemical Engineering, 2026)

Lignin-based sunscreen materials: A review of mechanisms of action, precision modification strategies, multifunctional application advances, challenges and prospects - Yuan Chen; Zibo Yu; Rui Tang; Jiayi Sun; Xigao Jian; Jinyan Wang; Xiaozhou Zhang; Xing Wang; Jingyu Xu (Journal of Environmental Chemical Engineering, 2026)

Innovations in arid land salinization management: Xinjiang's evolving paradigm for saline-alkali land governance - Jiandong Yu; Jihong Zhang; Zhenhua Wang; Li Guo; Jinzhu Zhang; Zhengjiang Feng; Yue Wen; Rui Chen; Xiaoguo Mu (Journal of Cleaner Production, 2026)

Erosion control performance of geomats on silty soil slopes under simulated rainfall - Rui Zhang; Xiwei Zhang; Kang Chen; Yipeng Guo; Yanhua Yu; Huanhua Cai (Geotextiles and Geomembranes, 2026)

Copper isotope perspective on sulfide-silicate liquid immiscibility - Li-Juan Zhu; Lie-Meng Chen; Peter C. Lightfoot; Sheng-Ao Liu; Dan-Dan Li; Song-Yue Yu; Rui-Zhong Hu (Geochimica et Cosmochimica Acta, 2026)

Magnesium isotope geochemistry in continental flood basalts: implications for mantle source heterogeneity - Sakine Moradi; Lie-Meng Chen; Peter C. Lightfoot; Kang-Jun Huang; Qiao Su; Song-Yue Yu; Li-Juan Zhu; Rui-Zhong Hu (Geochimica et Cosmochimica Acta, 2026)

A detoxifying multi-strain probiotic formula attenuates toxicity induced by heavy metals and phthalates - Rui Xiao; Yaqi Yu; Deshan Ning; Zehua Chen; Chuguang Ning; Leilei Yu; Shumao Cui; Jianxin Zhao; Gang Wang; Yong Zhou; Xing Jin (Food Research International, 2026)

Systemic crosstalk between liver and brain is associated with microplastic-induced neurobehavioral toxicity in zebrafish - Zhimin Xu; Zheng Lin; Yifan Wang; Lei Wang; Runtong Huang; Rui Du; Xinya Kang; Xueqing Chen; Shaohua She; Zhihao Xu; Shuai Xiao; Renqiang Yu (Environmental Pollution, 2026)

Hydrophobization engineering in nitrile hydratase-nicotinamidase cascade system: Promoting multi-tunnel formation for enhanced niacin biosynthesis - Yinbiao Xu; Rui Wang; Chaofan Li; Yu Liu; Xinyue Zhang; Hao Fu; Zongda Chen; Pei Zhou; Yang Sun; Hua Li; Yupeng Liu (Chemical Engineering Journal, 2026)

Developmental light colour influences adult phototaxis and locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Zi-Yu Guo; Xu-Hui Guo; Sheng-Yu Hou; Ke-Jing Feng; Yu-Xin He; Han-Ning Wu; Xin-Hui Chen (Behavioural Processes, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Enhancing photosynthesis and stress tolerance of the cyanobacterium Nostoc sphaeroides by adaptive laboratory evolution via dry-wet cycles - Zhen Chen; Rui Liu; Yu-Qing Peng; Zhang-Zhuo-Ya Wang; Yong-Qi Yin; Sheng Du; Yu-Jie Jin; Kui Xu; Fei-Fei Li; Wei-Zhi Li; Shan Zhang; Hua-Hua Yue; et al. (Algal Research, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Model scale approach to assess the seakeeping performance of a foil-assisted unmanned catamaran - Bing Zheng; Qiaowen Yu; Shigang Wang; Weimin Chen; Zhiyuan Geng; Rui Deng (Ocean Engineering, 2026)

Drought-induced disaster Chains: A global perspective of propagation probabilities and mitigation priorities - Huicong Jia; Fang Chen; Rui Li; Yu Chen; Lei Wang (Journal of Cleaner Production, 2026)

Microbiota-responsive BmMBF2-11 limits dysbiosis and promotes intestinal immune homeostasis in the silkworm - Qingxiu He; Rui Yang; Huawei Liu; Huanan Zhu; Yu Zhang; Hao Chen; Qingsong Liu; Guangcheng Huang; Qingyou Xia; Ping Zhao (Insect Biochemistry and Molecular Biology, 2026)

Fabrication and physicochemical characterization of SPI-gallic acid-guar gum ternary complexes: Insights into covalent bonding and structural tunability - Mingze Xu; Chen Gu; Khubaib Ali; Peipei Yin; Chang Liu; Rui Sun; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Chemistry, 2026)

Plasma organophosphate ester exposure-associated microRNA expression profiles and their functional analysis in Chinese healthy adults - Xulin Zhang; Zirui Zhang; Yuxin Xu; Jiajia Zhu; Guang Chen; Rui Zeng; Wending Li; Xuedan Xu; Yu Yuan; Tao Jing; Tangchun Wu; Pinpin Long (Environmental Research, 2026)

Centrifuge modeling of static liquefaction in completely decomposed granite fill slopes - Zhun Liu; Yu Zhao; Teng Liang; Fan He; Rui Zhang; Zhuang Yan; Daosheng Ling; Liangtong Zhan; Yunmin Chen (Engineering Geology, 2026)

Mechanical-thermal -electrical-magnetic integration in aramid composites via binary inorganic synergy - Junchao Ren; Chenglei Huang; Rui Tan; Jianlong Chen; Mengde Huang; Shijing Song; Chengyu Yu; Hanwu Lei; Lu Wang; Bin Li; Qingfa Zhang (Chemical Engineering Journal, 2026)

Two-level energy storage semi-interpenetrating hydrated salt gel for battery cooling and thermal runaway propagation mitigation - Rui Wei; Yuhan Xiao; Jianfeng Wang; Fuqiang Wang; Di-Lin Chen; Bowei Chen; Zipeng Su; Yongkai Jia; Ruixuan Qiu; Yiqun Liu; Quanqing Yu; Fen Liu (Chemical Engineering Journal, 2026)

Engineering Escherichia coli cell Factories for continuous 5′-cytidine monophosphate production via biofilm-anchored dual-enzyme cascade catalysis - Wenjun Sun; Shiya Zhu; Qiwei Dong; Shuyan Tang; Qingguo Liu; Yu Sha; Tianpeng Chen; Rui Wang; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Analysis of the species distribution and drug resistance of pathogenic microorganisms causing diabetic foot infections in Southwest China from 2020 to 2024: a retrospective cross-sectional analysis - Shangyu Zhang; Junchi Chen; Rui Sun; Yu Pan; Yusen Zhuo; Li Tang; Jianhua Zhu; Shuyang Li; Lin Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Development of a portable electrochemical sensor based on STAB-GN for simultaneous detection of chloramphenicol and enrofloxacin in foods - Rui Gao; Yongfeng Chen; Yu Su; Geoffrey I.N. Waterhouse; Xuguang Qiao; Yufeng Sun; Zhixiang Xu (Analytica Chimica Acta, 2026)

From species to therapeutic property: distribution differences of threatened Chinese medicinal plants under climate change - Yun-Han Chen; Rui Yang; Run-Han Jiang; Yu Xia; Ling-Feng Mao (Biodiversity and Conservation, 2026)

Incorporating Thermal Adaptation and Acclimation Improves Light‐Use Efficiency Modeling for Estimating Gross Primary Production in Tibetan Plateau Grasslands - Gaofei Yin; Jiangliu Xie; Yu Wang; Rui Chen; Yajie Yang; Dujuan Ma; Wenping Yuan; Qiaoyun Xie; Da Wei; Huai Chen; Xinwei Liu; Aleixandre Verger; et al. (Global Change Biology, 2026)
The optimal temperature for photosynthesis (Topt), the temperature at which photosynthesis peaks, is crucial for estimating gross primary production (GPP). Most models, however, apply biome‐specific Topt, overlooking the spatial and temporal variability driven by the genetic adaptation and interannual thermal acclimation of plants, thus introducing systematic error in GPP estimation. We mapped Topt of Tibetan Plateau (TP) grassland averaged over 1982–2018, using satellite‐derived near‐infrared reflectance of vegetation as a proxy of photosynthesis, and projected future Topt under different scenarios of shared socioeconomic pathways (SSPs) using space‐for‐time substitution. We assessed the effects of Topt adaptation on current GPP estimation and acclimation on projected GPP using a light‐use efficiency model (i.e., EC‐LUE model). The spatial heterogeneity of Topt was pronounced across the TP grassland, with higher values in the northeast and lower values in the southwest, averaging 9.32°C ± 3.15°C. Topt tended to increase from 2040 to 2080 across all SSPs, with the slowest increase under SSP1‐2.6 (0.015°C y −1 ) and the fastest increase under SSP5‐8.5 (0.061°C y −1 ). Incorporating Topt adaptation into the EC‐LUE model improved the accuracy of GPP estimation, with R 2 increasing by 7.19% and RMSE decreasing by 11.40%, compared to the model with a fixed Topt. In contrast, ignoring the adaptation of Topt led to systematically lower GPP values across 77.9% of the TP grassland, resulting in an overall reduction of estimated GPP by 7.07% (0.07 g C m −2 d −1 ). Ignoring the acclimation of Topt led to systematically higher projected GPP on the TP, ranging from 2.87% ± 8.96% (SSP1‐2.6) to 3.83% ± 5.97% (SSP3‐7.0) across different scenarios, covering more than 70% of TP regions. These findings highlight the necessity of incorporating both the adaptation and acclimation of Topt into GPP models to enhance the monitoring of the carbon cycle.

Analysis of Vortex-Induced Vibrations in a Test Production Riser Subjected to Internal Multiphase Flow - Qiang Fu; Liangjie Mao; Yu Chen; Rui Qin; Junlong Zhu (Journal of Marine Science and Engineering, 2026)
The natural gas hydrate production riser is the main passage for offshore hydrate production and transport. Its safe operation directly affects the production process. However, current hydrate production methods cannot avoid hydrate decomposition and formation inside the pipe. Hydrate phase change causes internal multiphase flow. Together with the external ocean current, it leads to more complex nonlinear vibration of the riser. Based on China’s gas hydrate trial production in the Shenhu area of the South China Sea, this study establishes a dynamic model of a production riser. The model considers hydrate phase change inside the pipe and vortex-induced vibration. It is solved using the Newmark-β method, and its validity is confirmed by CFD simulations. The results show that, under the combined action of ocean currents and internal multiphase flow, the riser exhibits a clear multi-frequency response in vortex-induced vibration. Its spatial trajectory is highly irregular. Specifically, hydrate phase change increases internal gas content and gas slippage, elevating fluid velocity. This reduces the riser’s structural stiffness and effective tension, altering the VIV response. In addition, lower top tension and higher slurry density, flow rate, and outlet backpressure delay hydrate decomposition. These factors also reduce the effective tension along the riser and increase its in-line deformation.

Responses of Phaeodactylum tricornutum to short-chain chlorinated paraffins: growth inhibition, photosynthetic damage and oxidative stress - Rui Shi; Wei Chen; Yujun Hu; Bingjian Chen; Xiaoxiao Yu; Hui Huang; Dan Wang; Shunxin Hu (Frontiers in Marine Science, 2026)
Introduction Short-chain chlorinated paraffins (SCCPs) have garnered increased attention due to higher persistence, bioaccumulation, long-distance transportation potential, and heightened toxicity to aquatic species and mammals. Methods This paper evaluated the toxic effects of SCCPs on P. tricornutum during a 96-hour acute exposure experiment, focusing on growth inhibition, photosynthetic parameters, and oxidative stress responses. Results Results showed that at the environmental concentration (0.001 mg/L), SCCPs exerted no significant effects on the growth and photosynthesis of P. tricornutum . However, higher concentrations (2, 4, and 8 mg/L) exposure resulted in a pronounced, dose-dependent growth inhibition, with inhibition rates reaching 37.43%, 53.25%, and 54.47% (p < 0.05), respectively. SCCPs stress disrupted the photosynthetic system, leading to reduction in the contents of chlorophyll a, chlorophyll c and carotenoids. Key photosynthetic pigments were depleted, and Photosystem II (PSII) efficiency (Fv/Fm, Y(II), rETRmax) was markedly suppressed. Furthermore, SCCPs exposure induced oxidative damage, as evidenced by elevated reactive oxygen species (ROS) and malondialdehyde (MDA) levels. Mitochondrial damage led to insufficient energy supply, resulting in decreased antioxidant enzyme activity. Discussion Collectively, these findings establish that high concentrations of SCCPs inhibit algal growth and photosynthesis through a dual mechanism involving direct photosynthetic disruption and the induction of oxidative damage.

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Numerical prediction on cavitation characteristics of a marine propeller in oblique flow without and with hull wake effects - Yu Sun; Shengyao Ge; Rui Wu; Wenyu Chen; Han Han; Depeng Ma; Huan Ping (Ocean Engineering, 2026)

Dynamic analysis for monopile offshore wind turbine under combined wind-wave-seismic loading: Effects of clay cyclic degradation and shakedown - Kehao Chen; Rui Pang; Cun Hu; Long Yu; Tianju Wang; Yang Zhou; Bin Xu (Ocean Engineering, 2026)

Phosphorus limitation drives the deterministic assembly of dissolved organic matter and microbial activity in surface waters of urban lakes - Wei Yu; Pingping Fan; Haiquan Yang; Wenhao Li; Guomin Han; Jifei Hou; Rui Liang; Jingan Chen; Jie Li; Xuede Li (Organic Geochemistry, 2026)

SgPAP27b, a purple acid phosphatase, confers aluminum tolerance in Stylosanthes guianensis through membrane lipid remodeling - Jianyu Zhang; Jinhui Lv; Chun Liu; Ranran Xu; Yu Liu; Rui Huang; Rongshu Dong; Pandao Liu; Zhijian Chen (Journal of Hazardous Materials, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Sn2+ doping-induced activation of inert adsorption sites in Li/Al-LDHs for selective lithium extraction from brines - Rui Zhang; Chenlu Yan; Jun Chen; Ting Wei; Jianguo Yu; Sen Lin (Chemical Engineering Journal, 2026)

Integrating ensemble learning and rocky desertification indices improves accuracy and interpretability of soil thickness prediction in karst landscapes - Fayong Fang; Ruyi Zi; Tingsheng Chen; Qilian Zhu; Zhen Han; Rui Hou; Wanyang Yu; Longshan Zhao (CATENA, 2026)

Technological evolution and industrial scaling of Spirulina in China: a four-decade review - Kexin Xu; Ronglian Xing; Kang Wang; Song Qin; Zhili Yu; Hongxia Zhang; Rui Li; Zhen Yu; Lihong Chen (Journal of Applied Phycology, 2026)

Integrative Analysis the Role of ENG as a Metabolic and Macrophage-Related Gene in Hepatocellular Carcinoma - Songsong Fan; Yuhong Tang; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Weidi Yu; Chen Chen; Shunyi Wang; Shengjie Jin; Guoqing Jiang; Chi Zhang; et al. (Biochemical Genetics, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Promoting Aquatic Animal Health and Water Quality: A Systematic Review on Probiotics, Prebiotics and Synbiotics in Aquaculture - Yaxin Wen; Miao Wang; Haoran Wang; Shilin Liu; Ronglian Xing; Hongxia Zhang; Lihong Chen; Rui Li; Zhen Yu (Fishes, 2026)
Background: Aquaculture, a vital component of global food security, faces sustainability challenges due to intensive farming practices, including water pollution, disease outbreaks, and antibiotic overuse. Probiotics, prebiotics, and synbiotics have emerged as eco-friendly alternatives to antibiotics. However, research results remain heterogeneous across aquatic species and intervention strategies. Methods: Following PRISMA 2020, we searched two databases (up to January 2026) for in vivo trials. Two reviewers screened and extracted data, and 177 eligible studies were ultimately included, covering single-/multi-strain probiotics (SSP/MSP), live/inactivated microbial preparations, and diverse synbiotic formulations. Results: Among 177 studies, Bacillus spp. were the most widely reported and effective probiotic strains. MSP and synbiotics exhibited superior efficacy in boosting aquatic animal growth performance and disease resistance over SSP in 68% of the included trials. Probiotics act through the competitive exclusion of pathogens, immune modulation, and enhanced digestive enzyme activity; prebiotics selectively stimulate beneficial gut microbiota, improving nutrient absorption and immune function through metabolites such as short-chain fatty acids; synbiotics combine the advantages of both, exerting synergistic effects. Furthermore, as water additives or fermented feed ingredients, probiotics reduce nitrogenous waste and organic pollutants, contributing to bioremediation. Conclusions: All three additives are effective. Standardized application protocols and long-term trials are needed for sustainable aquaculture. This review provides a unified evidence-based foundation for the rational use of these additives in aquaculture.

Ferrate-assisted nonthermal plasma for efficient PFOA degradation in landfill leachate: Mitigating bulk organic interference and enhancing application potential - Changtao Chen; Zhuofan Yu; Rui Zhang; Xuetong Yang; Qintong Wang; Yuxian Ji; Xiaoyu Cheng; Jun Li; Anton Nikiforov; Stijn W.H. Van Hulle; Bo Lai (Water Research, 2026)

Nutrient regimes shaping the diatom-dinoflagellate interdecadal succession in coastal temperate waters of China - Kan Chen; Keqiang Li; Guangshen Tan; Peiyi Gao; Guangmin Zhen; Rui Yang; Kunlong Yu; Xiansheng Zhang; Xiaoru Cui; Dongliang Lu; Shanqiao Chen; Eric P. Achterberg; et al. (Water Research, 2026)

Upcycling anaerobic digestion methane to single-cell protein as a low-carbon strategy - Pan-Long Lv; Qing-Rui Hu; Yu-Yang Hu; Wenjing Gong; Qian Li; Rong Chen (Resources, Conservation and Recycling, 2026)

An Integrative morphology–hormone–transcriptome analysis of uniconazole induced internode shortening in Paeonia lactiflora - Le Chen; Zhijun Dong; Rui Zhao; Yanfang Ma; Liyuan Chen; Yuxuan Wang; Jaime A. Teixeira da Silva; Xiaonan Yu (Plant Science, 2026)

Integrated metabolomics and transcriptomics analyses reveal the molecular mechanism of anthocyanin accumulation in veins and leaves of Broussonetia papyrifera under cold stress - Xiangxue Yu; Rui Ni; Dingguo Zhang; Bo Chen; Qian Li; Ziyu Yang; Chenjing Li; Fuyuan Liu; Yongtao Xia; Guoqing Hou; Guoping Wang; Pengzhi Mao; et al. (Plant Science, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Dynamic hydrogen-bond-driven thorium ion traps in sodium alginate/tannic acid beads - Dingyang Chen; Chaofan Wang; Yu Yu; Zixu Ren; Rui Zhao (Journal of Hazardous Materials, 2026)

A new method for planning long-distance trails using wilderness quality mapping and trajectory data: A case study of the Taihang Mountain National Forest Trail in China - Yunmiao Chen; Yue Cao; Zhangqian Ye; Tao Liu; Pei Wang; Yunshuang Feng; Lingyun Liao; Mingyang Lv; Zhicong Zhao; Alan E. Watson; Steve Carver; Changjia Li; et al. (Journal of Environmental Management, 2026)

Drivers of CO2 and CH4 fluxes from shallow lakes and prediction based on climate factors under global warming - Zhentao Wu; Hui Liu; Fan Yang; Rui Ran; Huimin Yu; Haonan Xu; Danyun Chen; Geng Wang; Xiaobing Pang (Journal of Environmental Sciences, 2026)

Dual-Regulated Ru by alloying and Metal-Substrate interaction for Energy-Efficient hydrazine Oxidation-Paired hydrogen production - Qijing Zhang; Hongxia Yu; Siyi Wang; Haibo Li; Suyuan Zeng; Rui Li; Qingxia Yao; Qi Zhang; Ruru Chen; Lijian Meng; Konggang Qu (Fuel, 2026)

H₂-rich syngas from synergistic steam gasification of biomass with spent LIB cathodes: Catalytic kinetics and metal recovery - Ran Jiao; Lijie Sun; Bowen Li; Xinran Zhou; Yifei Xu; Yu Chen; Fenglei Qi; Xiaohao Liu; Rui Diao; Zhenting Zha; Peiyong Ma (Chemical Engineering Journal, 2026)

Multiplex PCR and nanopore sequencing reveal the genetic stability of Hantaan virus in Xi’an, China - Hailong Chen; Peng Zhang; Xiaoyue Chu; Yangni Deng; Mengying Yu; Leile Zhang; Quanli Du; Yuewen Han; Yujie Yang; Zerun Xue; Shuling Li; Rui Wu; et al. (Archives of Virology, 2026)

Comprehensive observations of carbonyls in the Northern slope of the Tianshan Mountains: Characteristics, reactivity and sources - Kexin Wang; Minghao Dong; Hanran Liu; Xin Zhang; Yunfeng Li; Yafei Wang; Rui Gao; Jingjing Zhang; Yurong Li; Yu Chen; Zhaojiang Li (Air Quality, Atmosphere & Health, 2026)

A New Species of Diaporthe Section Betulicola (Diaporthomycetidae, Diaporthales) From China - Yi Lan Jin; Xing Yu Luo; Kamran Habib; Yu Lin Ren; Qing Yang; Li Li Liu; Chanhom Loinheuang; Yang Chen; Qi Rui Li (New Zealand Journal of Botany, 2026)
A new species in Diaporthaceae, Diaporthe fengtaiensis sp. nov., is described and illustrated from Southwestern China. A comparative morpho‐anatomical study and multilocus phylogenetic analysis (ITS, CAL , HIS , TEF1‐α , TUB2 ) confirmed its position within the section Betulicola of the genus Diaporthe . The taxon is characterized by immersed ascomata (270–420 × 290–410 µm), relatively large asci (70–115 × 9.5–13.5 µm), and 1‐septate, fusiform ascospores (18.5–25.6 × 4.5–6.5 µm). Its positioning in a separate branch in the phylogenetic tree makes it distinct from the other known species of the section. A complete taxonomic treatment, based on two collected specimens, is provided along with molecular phylogenetic analyses.

Tracking the eyes to track decline: Global eye movement similarity as a novel neuropsychological marker of mild cognitive impairment - Zhan Wang; Hong-Zhou Xu; Fang Fang; Xue-Rui Peng; Ying-Chen Liu; Zhi-Jun Zhan; Jing Yu (GeroScience, 2026)

SEAF-Net: A Sustainable and Lightweight Attention-Enhanced Detection Network for Underwater Fish Species Recognition - Yu-Shan Han; Sheng-Lun Zhao; Chu Chen; Kangning Cui; Pingfan Hu; Rui-Feng Wang (Journal of Marine Science and Engineering, 2026)
This study presents SEAF-Net, a lightweight and efficient detection network designed for low-contrast and highly dynamic underwater environments. Built upon YOLOv11n, SEAF-Net introduces three complementary structural enhancements: (1) Omni-Dimensional Dynamic Convolution (ODConv) to improve adaptive modeling of multi-scale and directional texture variations; (2) SimA-SPPF, which embeds the SimAM attention mechanism into the SPPF module to enable neuron-level saliency reweighting and effective suppression of complex background interference; and (3) GhostC3k2 to reduce redundant computation while preserving sufficient representational capacity. Evaluated on a standardized 13-class underwater fish dataset under a unified training and evaluation protocol, SEAF-Net achieves 6.1 GFLOPs, 92.683% Precision, 88.459% Recall, 93.333% mAP50, 73.445% mAP, and a 90.522% F1-score. Compared with the YOLOv11n baseline, SEAF-Net improves F1-score and Recall by 0.510% and 0.575%, respectively, while reducing computational cost by approximately 6%, demonstrating a favorable accuracy–efficiency trade-off under lightweight constraints. Ablation results further confirm that SimA-SPPF plays a dominant role in background suppression, ODConv consistently enhances deformation and directional texture modeling, and GhostC3k2 effectively controls computational overhead without degrading detection accuracy. To assess deployment feasibility, additional test set evaluations were conducted under deployment-oriented conditions using resource-limited hardware, yielding an F1-score of 88.54%. This result confirms that the proposed model maintains stable detection performance and robustness beyond training and validation stages. Overall, SEAF-Net provides an effective balance of accuracy, efficiency, and robustness, offering practical support for low-carbon, scalable, and sustainable intelligent aquaculture monitoring and underwater ecological assessment in real-world environments.

Reinforcement-Learning-Based Adaptive PID Depth Control for Underwater Vehicles Against Buoyancy Variations - Jian Wang; Shuxue Yan; Honghao Bao; Cong Chen; Deyong Yu; Jixu Li; Xi Chen; Rui Dou; Yuangui Tang; Shuo Li (Journal of Marine Science and Engineering, 2026)
Underwater vehicles performing sampling tasks often encounter significant buoyancy variations due to payload adjustments and environmental changes, which severely challenge the stability and accuracy of controllers. To address this issue, this paper proposes a hybrid control framework that integrates Proximal Policy Optimization (PPO) with adaptive PID tuning. The framework employs PPO to dynamically adjust PID parameters online while incorporating output saturation, stepwise quantization, and dead zone filtering to ensure control safety and actuator longevity. A dual-error state representation—combining instantaneous error and its derivative—along with actuator command buffering is introduced to compensate for system lag and inertia. Comparative simulations and experimental tests demonstrate that the proposed method achieves faster convergence, lower steady-state error, and smoother control signals compared to both conventional PID and pure PPO-based control. The framework is validated through pool tests and field trials, confirming its robustness under realistic hydrodynamic disturbances. This work provides a practical and safe solution for adaptive depth control of sampling-capable AUVs operating in dynamic underwater environments.

Multilayer hydrogel thermal management for high-efficiency solar cells - Rui Guo; Haotian Ding; Haoyu Pan; Yu Chen; Jiajun He; Huan Xing; Fei Xu; Jun Chen; Shaochun Tang (Science Bulletin, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

Drivers of biogenic secondary organic aerosols in Eastern China: Evidence from machine learning and high-resolution measurements - Kun Zhang; Meng Xiu; Xiaohui Bi; Yanan Yi; Rui Li; Biao Zhou; Ruixin Pan; Hui Chen; Jian Zhen Yu; Li Li (Journal of Hazardous Materials, 2026)

Constructing a 3D Bi2WO6/Cd0.3Zn0.7S heterojunction to enhance photocatalytic CO2 reduction efficiency - Lele Niu; Xinrui Liu; Xuxi Liu; Juan Yu; Rui Chen; Kaixuan Yang; Le Chen; Mengyuan Hu; Jiang Wu; Ahmad Hosseini-Bandegharaei (Journal of Environmental Chemical Engineering, 2026)

Multichannel charge separation induced by multiple internal electric fields in ReS2/CoSx/CdS hollow nanostructures for efficient photocatalysis - Qi-Rui Zhang; Yu-Long Wang; Zhi-Hao Deng; You-Long Chen; Si-Jing Ding; Liang Ma (Journal of Environmental Chemical Engineering, 2026)

Comparative study by microwave, fixed-bed and rotary kiln pyrolysis of oily sludge: Petroleum hydrocarbons, N-/S-/Cl-containing pollutants and heavy metals - Jiantao Li; Hongdi Yu; Fawei Lin; Shupeng Zhang; Zizhen Niu; Zhihua Liu; Rui Zhang; Guijian Liu; Xiaojiang Shen; Beibei Yan; Guanyi Chen (Journal of Environmental Chemical Engineering, 2026)

Infrared spectroscopy combined with deep learning to describe the textural properties of cooked rice from raw materials: revealing spectral variations and internal correlations during processing - Rui Tang; Ting Yu; Zi Li; Junru Wu; Xiaoming Zheng; Leiqing Pan; Yang Chen; Kun Duan; Hui Dong; Weijie Lan (Food Control, 2026)

Enhancing identification confidence in non-targeted screening of emerging contaminants via an ensemble retention time prediction model: Applications in screening and ecological risk assessment - Ye Liu; Hua-Chun Liu; Tian-Hong Chen; Jian-Ping Deng; Rui-Fang Fan; Hong-Xuan Kuang; Yun-Jiang Yu (Environmental Pollution, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

Molecular epidemiology and clinical characteristics of human adenovirus in children in Hangzhou (2022–2023) - Qin-rui Lai; Wei Chen; Guo-feng Yu; Ya-jun Guo; Shi-qiang Shang; Wei Li (Archives of Virology, 2026)

Correction to: Assessing the distribution pattern of Saussurea medusa under climate change using an optimized MaxEnt model in Qinghai‑Xizang Plateau - Jing‑Hua Chen; Rui‑Tao Yu (Environmental Monitoring and Assessment, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Structural characterisation of a novel polysaccharide from pseudostellaria heterophylla fibrous root and its anti-inflammatory and antioxidant activities in vitro - Meng-Yu Li; Hai-Tian Deng; Ming-Zhu Ye; Li-Li Lu; Hong-Yuan Chen; Wen Rui (Natural Product Research, 2026)

An unconventional topology of betacoronavirus membrane protein drives viral assembly - Rui Lyu; Kaili Li; Lingjiao Xiang; Yingjian Li; Yaotian Liang; Xue Tan; Xiaoya Huang; Yu Chen; Hongyu Deng; Junjie Hu (Science Bulletin, 2026)

Mechanisms of AMF-mediated correlation between nutrient uptake and soil micropatterns in sugar beet plants under rotational and continuous cropping soil environments - Rui Chen; Yonglong Liu; Xinyi Zhang; Gui Geng; Lihua Yu; Yao Xu; Jiahui Liu; Yuguang Wang (Journal of Cleaner Production, 2026)

Composite hydrogel microspheres modulate intestinal inflammation via releasing HA modified liposomes@4-OI targeting M1 macrophages - Shuanghong Yang; Ze Li; Guiwen Qu; Liting Deng; Liuqing Dou; Sicheng Li; Yitian Teng; Luqiao Huang; Haohui Li; Kang Chen; Jinpeng Zhang; Rui Ma; et al. (Chemical Engineering Journal, 2026)

Environmental impacts and optimization strategies for integrating carbon capture and anammox-based processes in municipal wastewater treatment under uncertain influent parameters - Rui Zhou; Ying Zhu; Qian Li; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Arbuscular mycorrhizal fungi inoculation enhances 15N uptake by rice via modifying rhizosphere and hyphosphere soil bacterial and fungal community and soil enzyme activity - Pei Chen; Yu Cheng; Rui Chen; Ning Wang; Jianguang Yu; Lihong Xue; Linzhang Yang (Plant and Soil, 2026)

Expression of Beta vulgaris betaine aldehyde dehydrogenase 1 (BvBADH1) confers salt tolerance in tobacco (Nicotiana benthamiana) - Ming Wei; Xiang-Yu Chen; Meng-Li Li; Hao Li; Xin-Rui Wu; Guo-Qiang Wu (Physiology and Molecular Biology of Plants, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Ligation-mediated circuit-driven cascade amplification with high utilization rate of template for lncRNA MALAT1 detection in cancer mice tissues - Yuyan Huang; Fan Huang; Qianqian Du; Rui Yu; Jingfeng Lan; Junwei Luo; Hongli Chen; Huige Zhang (Analytica Chimica Acta, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)